Cardiovascular metrics and transepidermal water loss in a high heat risk environment. (2nd February 2009) - Whitt, Michael D.; Handy, Rodney; Grow, Bryan; Balzer, Keith
Heat stress is currently primarily classified by environmental factors and not physiological factors. It is already known that certain cardiovascular metrics such as heart rate, stroke volume, blood pressure and vascular compliance undergo changes as the body traverses the different classifications of heat stress from heat oedema to heat stroke. However, there is no specific metric that provides a consistent indication for the onset of heat stroke. Twenty four subjects were observed over a 30-minute time frame performing exercise where WBGT equalled 27.5°C to determine if gender, activity-level or age had a significant effect on transepidermal water loss (TEWL) rate in addition to the relationship that the cardiovascular metrics had with TEWL rate. It was determined that heart rate, elapsed time exercising in the high temperature/humidity environment and age of subject all had significant effects on TEWL rate at a 95% confidence. Preliminary results demonstrate the possible existence of a relationship between sympathetic baroreflex sensitivity, cardiovagal baroreflex sensitivity and TEWL.